Strategy to Improve the Quality of Islamic Religious Education Teaching in the Digital Era - Nurcholis, Muhammad; Musa, Muhajir; Mabruri, Muhammad Santri; Arif, Muhammad Lukman (Al-Ilmu, 2025)
Improving the quality of Islamic Religious Education (PAI) teaching in the digital era is a challenge as well as an opportunity for educators. This study aims to analyze strategies that can be applied to increase the effectiveness of PAI teaching through the use of digital technology. The research method used is Systematic Literature Review (SLR), which allows systematic analysis of various previous studies relevant to this topic. The research stages include problem identification, formulation of research questions, and data collection and synthesis from various academic sources. The results of the study show that the application of technology in PAI teaching can improve the quality of learning by creating a more interesting, interactive, and flexible learning experience. However, the success of this strategy depends on the readiness of educators to adapt technology optimally. Therefore, some of the main strategies recommended include the selection of appropriate technology, increasing digital competence for teachers, and instilling ethical and moral values in the use of technology. With the right strategy, PAI teaching can be more effective, relevant to the times, and able to form a young generation who has a strong understanding of religion and good character.